Effect of anthelmintics on reproductive performance and first lactation culling rate in heifers - Mejía, M. E. (2009)
Female Holstein calves were treated with ivermectin from birth to first oestrus to study the effect of parasitic burden and anthelmintic treatment on reproductive and productive performance. First oestrus, age at first service and age at calving were advanced by 30, 70 and 110 days, respectively (P<0·05), in ivermectin-treated animals compared with controls. No significant differences were observed in the conception rate, the number of services and the characteristics of the newborn calves and any problems at calving between the two groups. Daily milk yield, fat content in milk during first lactation, and the concentrations of growth hormone, insulin-like growth factor type 1, insulin and prolactin in serum were similar in both groups of cows. Culling during the first lactation was more common in untreated (47 per cent) than in treated (11 per cent) cows (P<0·05).